The role of unexplained high serum alpha-fetoprotein (AFP) and human chorionic gonadotropin (hCG) levels in the second trimester to determine poor obstetric outcomes - Öztürk, Hümeyra; Erkaya, Salim; Altınbaş, Sibel; Karadağ, Burak; Vanlı Tonyalı, Nazan; Özkan, Demet (Galenos Yayinevi, 2014)
To investigate the relationship between gestational complications and high levels of maternal serum alfa-fetoprotein (MSAFP) and/or beta human chorionic gonadotropin (hCG) and to determine whether these markers are effective predictors of poor pregnancy outcomes.In this study, we enrolled a total of 679 women at 15-20 gestational weeks with MSAFP and hCG below or above 2.0 multiples of the median (MoM); of those, 200 women with normal MSAFP and hCG MoM formed the control group. Pre-eclampsia, intrauterine growth retardation (IUGR), preterm labor, preterm delivery, placental abruption, placenta previa, placenta accreta, preterm premature rupture of the membranes (PPROM), intrauterine fetal death, as well as neonatal and perinatal morbidity rates were evaluated.A significant relationship was found between adverse pregnancy outcomes and abnormal elevation of hCG and AFP levels in the second trimester. In cases of isolated elevation of hCG, preeclampsia and preterm labor/spontaneous preterm birth rate were slightly higher than in the control group (p=0.043, p=0.015), while IUGR, PPROM, placental abruption, and intrauterine fetal death rates were all similar (p=0.063, p=0.318, p=1.00, p=0.556). In case having an elevation in both markers, increased rate of obstetric complications have been observed. A significant relationship was found between the high levels of maternal serum AFP and hCG MoM and poor pregnancy outcomes like preeclampsia, IUGR, PPROM, intrauterine fetal death (p=0.003, p=0.001, p=0.040, p=0.006).To our knowledge, up to now, no definitive follow-up and treatment protocols have been established for patients at increased risk. In light of these findings, it is recommended to inform and educate patients about the most likely signs and symptoms of complications, to make more often antenatal visits, to perform more frequent ultrasound examination (fetal growth, AFI, etc.), NST, arterial/venous doppler, biophysical profile, and cervical length measurements in high-risk group.
Keywords: Clinical Investigation; 3. Good health